STATUS OF INSECTICIDE RESISTANCE IN LEAFHOPPER, AMRASCA BIGUTTULA BIGUTTULA (ISHIDA) ON COTTON - RAJWINDER KAUR SANDHU,; B. K. KANG, (The Bioscan, 2015)
Laboratory studies were carried out to investigate the development of resistance towards recommended insecticides in cotton leafhopper, Amrasca biguttula biguttula collected from four different locations viz., Ludhiana, Muktsar, Mansa and Abohar of Punjab. Five insecticides viz., imidacloprid, acetamiprid, dimethoate, monocrotophos and triazophos were tested. Among different populations, Abohar population was found to be the least susceptible with LC 50 values ranging from 0.0020-0.0496 per cent whereas Ludhiana population was found to be more susceptible with LC 50 values ranging from 0.0012-0.0255 per cent to all the insecticides tested. Among different insecticides, imidacloprid with LC 50 values ranging from 0.0012 to 0.0020 per cent showed maximum toxicity followed by acetamiprid, dimethoate and monocrotophos while triazophos was found to be least effective insecticide with LC 50 values ranging from 0.0255 to 0.0496 per cent. Small differences in the susceptibility from the baseline LC 50 values against all the tested insecticides indicated that there are no serious levels of resistance (2.12-5.11 x) in A. biguttula biguttula with respect to these insecticides in Punjab.